PERAN DIPLOMASI KOMERSIAL KJRI KARACHI DALAM MENDUKUNG EKSPOR MINYAK SAWIT INDONESIA KE PAKISTAN: ANALISIS BERDASARKAN KERANGKA FAR - Dewi, Sari Amalia; Priyokusumo, Nayottama Danendraduta (Moestopo Journal of International Relations (MJIR), 2025)
This research examines the commercial diplomacy conducted by the Consulate General of the Republic of Indonesia in Karachi to support Indonesia’s palm oil exports to Pakistan, using Naray’s FAR — facilitation (F), advisory (A), and representation (R) — commercial diplomacy framework. The method used in this research is a descriptive qualitative approach, employing literature studies and interviews as data collection techniques. Findings demonstrate that the Consulate General supported Indonesian palm oil exporters through business facilitation efforts, such as organizing business matching sessions to foster trade interactions. Additionally, the Consulate General provided advisory services through market intelligence and research-based reporting to exporters and government stakeholders. Lastly, its participation in promotional events and advocacy campaigns illustrates the representation role in enhancing Indonesia’s commercial presence in Pakistan. This study highlights how the 'FAR' framework effectively operationalizes commercial diplomacy in supporting export strategies.